Web application authentication using ZKP and novel 6D chaotic system - Shatha J. Mohammed; Sadiq A. Mehdi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Text password has long been a dominant approach to user authentication used by a huge quantity of Internet services. Web applications are now widely used for the implementation of a range of significant services. The securing of such applications has thus become a significant process. Currently the frequent use of passwords and the need for them make them more vulnerable to theft or guesswork. In the proposed research, the researcher designed an algorithm that has the ability to perform registration or to access web applications safely. The researcher designed an algorithm in the proposed research, which has the ability to securely perform registration or access web applications. The proposed idea based on the notion of Zero-knowledge proof. A complex generation of random number initiated by proposed novel 6D-Hyper chaotic system. The bottom line is that both parties (web application, user), have a secret number. These two numbers used to do the process of registration without requiring a password. Results from the research showed the importance of the proposed method by which the keys were managed and distributed in a safe and effective way.